Gene editing for advanced therapies Governance, policy and society - Garden, Hermann (OECD Science, Technology and Industry Working Papers, 2018)
Gene editing aims to modify the genetic sequence at a precise genomic location. Recent breakthroughs in gene editing techniques such as the clustered regularly interspaced short palindromic repeats (CRISPR) system have ushered in a new era for gene editing and health innovation. The purpose of the Expert Meeting (6-7 July 2017, Federal Ministry of Education and Research, Berlin, Germany) was to explore the core scientific, legal, regulatory and societal challenges facing the responsible development and use of gene editing in somatic cells for advanced therapies. Experts noted that the trajectory of gene editing in research and development and the uptake of future therapies in the clinical setting remain unclear due to uncertainties in the scientific, regulatory, and economic landscapes. Many policy issues are also raised in the context of other emerging technologies. Governance must cope with a moving technical frontier and some level of uncertainty around risks and benefits